POTENSI EKSTRAK DAUN MIMBA (Azadirachta indica Juss ) SEBAGAI PESTISIDA NABATI TERHADAP MORTALITAS WERENG HIJAU (Nephotettix sp.) PADA TANAMAN PADI (Oryza sativa L. ) - Ni Putu Setiari; Cokorda Javandira; Luh Putu Yuni Widyastuti (Agrofarm: Jurnal Agroteknologi, 2022)
Food security is one of the problems of national food which is very important to avoid food crisis. Plant pests is one of the obstacles to increase agricultural production, greatly affect the rice (Oryza sativa L.) In the agricultural production is inseparable from the name of the production factors one of which is the use of pesticides but its use is extremely unwise evidenced by the number of victims, as a result of chemical residues. Green leafhopper (Nephotettix sp.) is a member of Family Cicadellidae, Order living in the rice plant. An important role is as vector Tungro virus. Pesticide from neem plant is environmentally friendly pesticides that can be used in organic farming. Insects that feed on the leaves, the leaves of plants or directly affected by the extra spray neem growth will be impaired metabolism, interfere with the process of insect metamorphosis so metamorphosis be incomplete until severe experiencing this mortality. Research do in Banjar Penatahan, Bangli regency, Bali. The study design used was completely randomized design (CRD) each treatment was performed 5 replicates where all the data is analyzed by a Single Variant Data Analysis (ANOVA).Giving different concentrations of botanical pesticides, does not describe an increase in mortality green leafhopper. This shows that the power of the pesticide plant is not only focusing on the mortality of insects alone, but also acts as an anti feedant (prevent appetite) and repelant (reject the presence of insects). Neem leaf extract is a very real influence as a pesticide plant in green leafhopper pest control (Nephotettix sp.).